STUDI FENOMENOLOGI PADA ASPEK KOMPETENSI SOSIAL EMOSIONAL PENGALAMAN GURU KIMIA SMA NEGERI 4 SINGARAJA - Ni Putu Widhi Linda Rahayu; I Wayan Redhana; Ida Bagus Nyoman Sudria (CHEDS: Journal of Chemistry, Education, and Science, 2026)
This study aims to explore the lived experiences of chemistry teachers in integrating Social Emotional Competence (SEC) into the learning process amidst the challenges of a crowded school environment and a suboptimal science learning climate. The study used a qualitative approach with phenomenological methods to uncover how SEC manifests in emotional management, social interactions, and decision-making in chemistry lessons at Singaraja 4 Public Senior High School. Data were collected through observation of the learning process, in-depth interviews, and documentation of student learning outcomes. Data validity was achieved through technical and source triangulation to enhance the credibility of the research findings. The results indicate that chemistry teachers are able to consistently integrate Social Emotional Competence into their learning despite limited facilities and classroom crowding. Teachers' social awareness and relationship skills are evident through their attention to students' psychological well-being as an effort to increase motivation to learn chemistry. In terms of self-management, teachers demonstrate stable emotional regulation skills through educational reprimands that respect students' rights. Furthermore, responsible decision-making is realized through a transparent and fair assessment system that considers aspects of the process, product, and student attitudes. The research findings confirm that the integration of KSE by chemistry teachers plays an important role in creating a supportive, humanistic, and meaningful learning environment, thereby supporting the improvement of the quality of chemistry learning in schools.learning environment that supports the holistic development of students' character. Keywords: Phenomenological Study, Social Emotional Competence (SEC), Chemistry Teachers.